Pemaknaan e-commerce bagi pedagang konvensional: Studi fenomenologis di pasar tradisional - Saida, Mukhammad Fahmi Ulum (Maliki Interdisciplinary Journal, 2025)
The digital transformation in the trade sector has encouraged many business actors to adopt e-commerce as part of their business strategy. However, for conventional traders in traditional markets, this shift impacts not only the economic aspect but also social and cultural values rooted in local practices. This study aims to explore how traditional market traders in Pasar Besar Malang perceive the presence of e-commerce in their daily business activities. Using a qualitative approach with a phenomenological method, the research involved in-depth interviews with ten traders from various sectors within the market. The findings reveal that some traders view e-commerce as an opportunity to expand their market reach, while others feel marginalized due to limited digital literacy and lack of access to technology. For many, e-commerce is not merely a transactional tool, but a symbol of changing times that challenges the values of kinship and trust that have long formed the foundation of trade interactions. These findings highlight the need for inclusive digital education and assistance programs, so that conventional traders in Malang can adapt sustainably within the evolving digital economic ecosystem.